Information adequacy of medicine package inserts in India: A critical evaluation - Bikramjit Barkondaj; Kaushik Mukhopadhyay; Suvajit Das; Chandan Chatterjee; Sonali Mukherjee; Avijit Hazra (Perspectives in Clinical Research, 2021)
Objectives: Package inserts (PIs) are used by physicians and other health-care providers as ready source of approved prescribing information. In India, they are subject to statutory regulations that specify the information to be provided under various headings. Uniformity of PIs with optimal level of information is desirable, the absence of which may lead to medication errors. This observational study aimed to evaluate the information adequacy and accuracy of PIs available in the Indian market. Materials and Methods: PIs of drugs marketed in India, and approved by United States Food and Drug Administration, were collected from various retail pharmacies through purposive sampling. The adequacy and accuracy of the information in each PI were evaluated with the help of a 25-item checklist prepared as per stipulations mentioned in statutory guidelines. Each required item of information was scored 1 if present and appropriate or 0 if absent or deemed incomplete or inaccurate. A total information adequacy score (IAS), with maximum value 25, was thereby calculated. Results: From the total 135 PIs analyzed, the median IAS was 17 (interquartile range 15–19). Deficiencies were observed under important headings. For example, “references” were mentioned in only 6.67% and “date of last updating” in only 19.26% of PIs. Other notable shortcomings were in “disposal” (not mentioned in 92.59%), “effects on ability to drive and use machines” (76.30%), “pharmaceutical incompatibilities” (66.67%), “shelf life” (62.96%), “excipients” (60.00%), and “overdose” (17.78%) information. Information on “generic name,” “composition,” and “indications” were however provided by all (100%) PIs. Conclusions: The information provided by PIs in India being inadequate, may not be able to serve as a reliable source of information.